2011
DOI: 10.2139/ssrn.1674384
|View full text |Cite
|
Sign up to set email alerts
|

The Business Model: Recent Developments and Future Research

Abstract: This article provides a broad and multifaceted review of the received literature on business models in which the authors examine the business model concept through multiple subject-matter lenses. The review reveals that scholars do not agree on what a business model is and that the literature is developing largely in silos, according to the phenomena of interest of the respective researchers. However, the authors also found emerging common themes among scholars of business models. Specifically, (1) the busines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

35
2,066
1
91

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 1,201 publications
(2,198 citation statements)
references
References 73 publications
35
2,066
1
91
Order By: Relevance
“…Based on these observations, Devinney et al (2000) suggest that the IR framework must incorporate the concept of 'transactional completeness', which they define as the condition when 'all the characteristics of the transaction can be priced as if on an open market' (Devinney et al, 2000, p. 682). This concept is similar to the understanding of a business model, which concerns how value is captured in a market (Zott, Amit, & Massa, 2011).…”
Section: Global Integration and Local Responsivenessmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on these observations, Devinney et al (2000) suggest that the IR framework must incorporate the concept of 'transactional completeness', which they define as the condition when 'all the characteristics of the transaction can be priced as if on an open market' (Devinney et al, 2000, p. 682). This concept is similar to the understanding of a business model, which concerns how value is captured in a market (Zott, Amit, & Massa, 2011).…”
Section: Global Integration and Local Responsivenessmentioning
confidence: 99%
“…Some clients may prefer to cooperate with specific employees because they have established relationships over time involving high degrees of trust (Løwendahl, 1997). To satisfy these different needs, IPSFs have developed multiple coexisting business models (Amit & Zott, 2001;Morris, Schindehutte, & Allen, 2005;Osterwalder, 2004;Osterwalder & Pigneur, 2009;Osterwalder, Pigneur, & Tucci, 2005;Zott & Amit, 2007;Zott & Amit, 2008;Zott, et al, 2011).…”
Section: Value Creation In Ipsfsmentioning
confidence: 99%
“…BM also inherits a systemic view since it is the architecture of strategic choices of a firm or a value network [6], [7]. Thus, BM of a value network should create complexity as a result of the choices made in order to deliver and appropriate value.…”
Section: Introductionmentioning
confidence: 99%
“…The concept gathered momentum to such an extent that traditional business models are being changed to networked business model. The networked nature of business is taken into account in the business model and business model innovation literature [Zott et al, 2011]. Examples include a business model canvas [Osterwalder and Pigneur, 2010], value networks [Allee, 2008], and resources and capabilities across organizational boundaries [Bouty, 2000].…”
Section: Business Models and Strategy In Business Networkmentioning
confidence: 99%
“…In this setting, one must consider the whole network and capture the interplay between the various components of the network, where each component can potentially be facilitated by a distinct business partner. Previous research has shown the cross-boundary nature of the business model operation [Zott et al, 2011], in which certain activities of a focal organization are performed by other business partners, suppliers or associates. This allows for the use of resources and capabilities available in the network through different operation arrangements such as outsourcing, and co-sourcing.…”
Section: Business Models Design For a Networked Operation: Strategic mentioning
confidence: 99%